2001
DOI: 10.1097/00002060-200112000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Bladder Management and Quality of Life After Spinal Cord Injury

Abstract: Individuals with impaired bowel and bladder control reported lower quality of life on several domains compared with those with independent control of bowel and bladder. Though the two groups did not differ in self-reported social integration, dependent individuals may have greater difficulty creating new social relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
1
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 37 publications
1
81
1
2
Order By: Relevance
“…Management of bowel and bladder is seen as paramount to independence. This is universally reported in the general literature 14,17,18 and also in cross-cultural features game studies, 16 demonstrating concurrent validation utilizing a new methodology.…”
Section: Discussionsupporting
confidence: 54%
“…Management of bowel and bladder is seen as paramount to independence. This is universally reported in the general literature 14,17,18 and also in cross-cultural features game studies, 16 demonstrating concurrent validation utilizing a new methodology.…”
Section: Discussionsupporting
confidence: 54%
“…In a longitudinal, observational, epidemiologic study performed on a neurogenic bladder population (n ¼ 46 271) encompassing 4168 persons with SCI, due to the observation of high incidences of urinary tract complications and hospitalizations among patients with neurogenic bladder, it was concluded that these patients might have suboptimal management. 7 In their study, Hicken et al 8 reported that individuals with impaired bowel and bladder control had lower QoL on several domains than individuals with independent control of bowel and bladder. In the light of this information, it is obvious that bladder management is one of the important components of the treatment in patients with SCI.…”
Section: Discussionmentioning
confidence: 97%
“…11 Kuo 12 also reported that incontinence was the most troublesome urinary problem of SCI during their study's follow-up. The severity and frequency of incontinence and its impact on quality of life has rarely been studied among patients with SCI.…”
Section: Introductionmentioning
confidence: 95%